Weather on Mount Everest during the 2019 summer monsoon. (17th March 2021) - Khadka, Arbindra; Matthews, Tom; Perry, L. Baker; Koch, Inka; Wagnon, Patrick; Shrestha, Dibas; Sherpa, Tenzing C.; Aryal, Deepak; Tait, Alex; Sherpa, Tenzing G.; Tuladhar, Subash; Baidya, Saraju K.; et al.
Abstract : Records from new high altitude weather stations reveal the meteorological conditions on Mt Everest during the 2019 monsoon. Using data from June–October, we show that the temperature, humidity and winds announce the arrival of the monsoon, with changes that amplify with elevation. The largest change is therefore at the summit, where we estimate that monthly mean air temperature increased by 5.5°C between June and July to average −19.1°C over the monsoon. Such warming takes temperatures into the realm of winter conditions on much lower mountains of the mid‐latitudes, illustrated with the well‐known Mount Washington observatory (1916m; New Hampshire, USA). Although other dangers of climbing Everest may be enhanced during the monsoon, the cold induced hazard is much reduced. A view of the South Col automatic weather station (7945m). The south summit of Everest is visible in the background. (Source: Eric Daft/National Geographic.)